RHETORICAL ANALYSIS OF HEDGES AND BOOSTERS IN ACADEMIC ARTICLES WRITTEN BY EFL WRITERS - Keivan Seyyedi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This study investigates the use of hedges and boosters, linguistic devices employed to express uncertainty or confidence, in academic writing, mainly focusing on the gendered differences in the context of English as a Foreign Language (EFL) research articles. The primary objectives are to explore variations in the application of hedges and boosters between descriptive and experimental EFL articles and to investigate disparities in their use among male and female EFL writers. Twenty EFL articles from Iranian international journals were selected, focusing on the rhetorical sections of Abstract, Introduction, Discussion, and Conclusion. The study employed descriptive data analysis, calculating the frequency and percentage of hedges and boosters per 1,000 words to examine the distribution and usage patterns across different sections and genders. The analysis revealed nuanced patterns in the distribution of hedges and boosters across rhetorical sections, with the discussion and conclusion sections exhibiting higher frequencies. Gender differences were identified, indicating that female writers tended to use more hedges, expressing uncertainty in their interpretations. In contrast, male writers exhibited greater confidence, particularly in the introduction and conclusion sections. This research contributes valuable insights into the rhetorical strategies of academic writing, emphasizing the role of hedges and boosters in shaping scholarly discourse. The study's focus on gendered language use in the EFL context provides a foundation for future research and considerations in language instruction and academic writing pedagogy. Despite limitations, including a specific geographical focus and a relatively small sample size, the study enriches our understanding of linguistic strategies in academic writing and calls for further exploration in diverse EFL contexts.